Hitches in Mandarin Stroke Writing / Ch’ng Looi Chin...[et al.] - Ch’ng, Looi Chin; Ting, Hie Ling; Chuah, Kee Man (2019)
Many learners especially beginners face difficulties in learning Chinese language. One of the toughest components in learning the language is the learning of character writing as the metacognitive of learning this language is far too different from their native language. This study aims to get a better insight on non-native beginner learners’ mistakes in stroke writing. A dictation was carried out to examine the 50 non-native undergraduates’ common mistakes in stroke writing. Test items were all common words that they have learnt in their Mandarin level 2 text book. Data revealed that the common stroke mistakes were Stroke, Misalignment, Stroke’s Shape and Nonexisting Strokes. The findings suggest the techniques of stroke teaching is crucial to rectify the existing mistakes and to make improvement on teaching and learning. Further studies are needed to investigate the effectiveness of teaching methods to cater non-native learners’ learning patterns to achieve accuracy in stroke writing.